An Efficient Templating Approach for the Synthesis of Redispersible Size‐Controllable Carbon Quantum Dots from Graphitic Polymeric Micelles. Issue 43 (7th September 2015) - Zhang, Jianming; Abbasi, Farshad; Claverie, Jerome
Abstract Access to high‐quality, easily dispersible carbon quantum dots (CQDs) is essential in order to fully exploit their desirable properties. Copolymers based on N‐acryloyl‐D‐glucosamine and acrylic acid prepared by reversible addition–fragmentation chain transfer (RAFT) polymerization are self‐assembled into micelle‐like nanoreactors. After a facile graphitization process (170 °C, atmospheric pressure), each micellar template is transformed into a CQD through a 1:1 copy process. These high‐quality CQDs (quantum yield=22 %) with tunable sizes (2–5 nm) are decorated by carboxylic acid moieties and can be spontaneously redispersed in water and polar organic solvents. This preparation method renders the mass production of multifunctional CQDs possible. To demonstrate the versatility of this approach, CQDs hybridized TiO2 nanoparticles with enhanced photocatalytic activity under visible‐light have been prepared.